2004
DOI: 10.1023/b:fina.0000020656.65653.79
|View full text |Cite
|
Sign up to set email alerts
|

The Past, Present, and Probable Future for Community Banks

Abstract: We review how deregulation, technological advance, and increased competitive rivalry have affected the size and health of the U.S. community banking sector and the quality and availability of banking products and services. We then develop a simple theoretical framework for analyzing how these changes have affected the competitive viability of community banks. Empirical evidence presented in this paper is consistent with the model's prediction that regulatory and technological change has exposed community banks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
134
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 299 publications
(146 citation statements)
references
References 85 publications
9
134
0
3
Order By: Relevance
“…Before deregulation, banking was a relatively mature market with stable or slowly growing demand, dominant product designs and process technologies, and a relatively limited variety of strategies. Deregulation reduced the entry barriers for new bank ventures and reshaped the competitive landscape in the industry (DeYoung et al, 2003). The transformation of the regulatory environment involved the deregulation of deposit accounts, major changes in capital requirements, and liberalization of geographic restrictions on interstate banking, all of which provided ample room for new bank entries and changed the competitive dynamics of the market.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…Before deregulation, banking was a relatively mature market with stable or slowly growing demand, dominant product designs and process technologies, and a relatively limited variety of strategies. Deregulation reduced the entry barriers for new bank ventures and reshaped the competitive landscape in the industry (DeYoung et al, 2003). The transformation of the regulatory environment involved the deregulation of deposit accounts, major changes in capital requirements, and liberalization of geographic restrictions on interstate banking, all of which provided ample room for new bank entries and changed the competitive dynamics of the market.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The transformation of the regulatory environment involved the deregulation of deposit accounts, major changes in capital requirements, and liberalization of geographic restrictions on interstate banking, all of which provided ample room for new bank entries and changed the competitive dynamics of the market. Research in organizational ecology has shown that events such as technological innovations or shifts in regulation or an economic depression can significantly affect the overall structure of the market (DeYoung et al, 2003). Whereas prior studies have typically focused on differences in industry structure across populations (in different regions, for example), this study focused on changes over time within a regional population (new banks in California), and investigated how changes in the dynamics of the market affected the market niche positioning decisions of new banks.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations